2014
DOI: 10.1104/pp.114.241521
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association in Tomato Reveals 44 Candidate Loci for Fruit Metabolic Traits  

Abstract: Genome-wide association studies have been successful in identifying genes involved in polygenic traits and are valuable for crop improvement. Tomato (Solanum lycopersicum) is a major crop and is highly appreciated worldwide for its health value. We used a core collection of 163 tomato accessions composed of S. lycopersicum, S. lycopersicum var cerasiforme, and Solanum pimpinellifolium to map loci controlling variation in fruit metabolites. Fruits were phenotyped for a broad range of metabolites, including amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
231
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(254 citation statements)
references
References 67 publications
13
231
3
7
Order By: Relevance
“…Unlike complex quantitative traits (such as flowering time) for which little epistasis has been detected (Buckler et al, 2009;Morris et al, 2013;Zuo and Li, 2014), variation in levels of metabolites, especially specialized metabolites, is predominately controlled by epistasis in both RILs (Kliebenstein et al, 2002;Loudet et al, 2003;Calenge et al, 2006;Lisec et al, 2008;Rowe et al, 2008;Gong et al, 2013) and natural populations (Chan et al, 2011;Chen et al, 2014;Sauvage et al, 2014;Dong et al, 2015;Matsuda et al, 2015). Similar results were observed between some of the loci identified in our study (Supplemental Figure 5 and Supplemental Table 3).…”
Section: Discussionsupporting
confidence: 75%
“…Unlike complex quantitative traits (such as flowering time) for which little epistasis has been detected (Buckler et al, 2009;Morris et al, 2013;Zuo and Li, 2014), variation in levels of metabolites, especially specialized metabolites, is predominately controlled by epistasis in both RILs (Kliebenstein et al, 2002;Loudet et al, 2003;Calenge et al, 2006;Lisec et al, 2008;Rowe et al, 2008;Gong et al, 2013) and natural populations (Chan et al, 2011;Chen et al, 2014;Sauvage et al, 2014;Dong et al, 2015;Matsuda et al, 2015). Similar results were observed between some of the loci identified in our study (Supplemental Figure 5 and Supplemental Table 3).…”
Section: Discussionsupporting
confidence: 75%
“…A number of accessions within the BIG and CER variety groups showed high fruit malate content, and several of these accessions also were present in the PIM group (Supplemental Figure 1). In this GWAS, we observed that a single region on chromosome 6 contained multiple SNPs that were highly associated with fruit malate content, consistent with previous results (Figures 1B and 1C; Sauvage et al, 2014). We therefore designated this locus TFM6.…”
Section: Combined Gwas and Bsa For Efficient Mapping Of Fruit Malatesupporting
confidence: 76%
“…Previously, Sauvage et al (2014) conducted an mGWAS study using 19 primary metabolites and 5995 SNPs among 163 tomato accessions. This led to the identification of 44 major polymorphic loci that control the variation of 19 primary metabolites in natural populations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several significant SNPs colocalized for the strongly correlated element pairs Ca and Sr (r = 0.79) as well as Mg and P (r = 0.71). Shared SNPs and colocalization of significant loci across multiple element traits suggest the possibility of tightly linked genes or genes with pleiotropic effects and have been documented in recent GWA studies, including experiments in tomato (Solanum lycopersicum; Sauvage et al, 2014) and rice (Zhao et al, 2011). In our analysis, we applied a conservative threshold in our MLMM implementation and identified SNPs from the most complex model, in which the P values of cofactors were below a defined threshold of 0.05.…”
Section: Discussion Ionome Profiling For Improved Sorghum Seed Qualitymentioning
confidence: 99%